Papermaking with tumeric and lemongrass leaves - Che Murad, Muhammad Imran; Mohd Fadil, Farid Danial; Zakaria, Nurul Aimi; Mohamed Zabidi, Zubainun; Alias, Ahmad Nazib (2024)
This study able to explores the use of turmeric and lemongrass leaves in papermaking. The objectives is to determine the best ratio for producing high-quality paper. In this study, 7 sample with different ratio were tested. The process of papermaking involved cutting, boiling, blending and then straining and drying the leaf mixture. The samples have the same amount of volume to ensure the sample have the same thickness and size. The samples were analyze for their quality based on air flow, solid filtration and tensile strength. Among the samples, the sample with ratio of 1:2 (turmeric to lemongrass) that has the best quality of paper due to the tensile strength and overall quality.